Psychogenic Depression Depending on Gender and Age Differentiation - Alena Gura (Journal of Global Pharma Technology, 2020)
The aim of the study is to analyze the factors that can be predictors of the development and progression of psychogenic depressions, as well as establish age and gender characteristics of their clinical options. The study included 140 people (70 females and 70 males) aged 30-70. Patients were divided into 2 groups: group 1 - 70 people diagnosed with psychogenic depression, aged 30 to 50, Group 2 - 70 people diagnosed with psychogenic depression, aged 50-70. In males of the younger age group, anxious (in 10 (28.7%) men) and dysphoric (in 13 (37.1%) men) variants of psychogenic depression were typical. In females, adynamic (in 14 (40%) females) and dysthymic (in 12 (34.2%) females) predominated. In patients of a older age, the gender differentiation of clinical variants of depression disappears, however, in this age group, both among males and females, the proportion of people with the hypochondriacal variant of psychogenic depression significantly increased by 2.6 times (OR = 3.32, 95% CI [1.36- 8, 14]). Thus, we established the presence of significant gender and age differences in the clinical course of psychogenic depressions and the frequency of factors that create the basis for the occurrence of depressive disorders, which should be taken into account when conducting appropriate complex therapy of the disease. Keywords: Gender characteristics of psychogenic depression, Clinical variants of psychogenic depression, Age-related features of psychogenic depression, Trigger factors of psychogenic depression.